Upconversion of Infrared Light by Graphitic Microparticles Due to Photoinduced Structural Modification - Rohin Sharma; Nishma Bhattarai; Rijan Maharjan; Lilia M. Woods; Nirajan Ojha; Ashim Dhakal (Advanced Photonics Research, 2024)
Recent reports of upconversion and white light emission from graphitic particles warrant an explanation of the physics behind the process. A model is offered, wherein the upconversion is facilitated by photoinduced electronic structure modification allowing for multiphoton processes. As per the prediction of the model, it is experimentally shown that graphite upconverts infrared light centered around 1.31 μm (0.95 eV) to broadband white light centered around 0.85 μm (1.46 eV). The results suggest that upconversion from shortwave infrared (≈3 μm, 0.45 eV) to visible region may be possible. The experiments show that the population dynamics of the electronic states involved in this upconversion process occur in the timescale of milliseconds.